Analyzing income inequality trends and variables for six high-income countries - Chrenka, Tyler, author; Tavani, Daniele, advisor; Berg, Marni, committee member (Colorado State University. Libraries, 2025)
This report examines the underlying drivers and evolution of income inequality across six high-income countries: France, Germany, Sweden, Canada, the United Kingdom, and the United States. This analysis takes the Gini Coefficient of each country and uses it as an overarching indicator of inequality. Then, pretax and post-tax distribution data is synthesized to determine which aspects of each country's economy are driving income inequality. This study distinguishes between inequality generated by market structures and inequality mitigated through redistributive taxation. The findings demonstrate that similar levels of overall inequality can arise from fundamentally different mechanisms. Countries such as Sweden achieve low inequality primarily through compressed labor-market wage distributions, which limits pretax dispersion, while Canada and France rely more heavily on redistributive taxation to reduce inequality after their market outcomes manifest. Germany's rising inequality is linked to increasing capital-income concentration combined with only moderate redistribution, while the UK's decline in inequality is driven largely by taxation of top earners rather than broad wage compression. The US stands out as the most unequal country, characterized by both high pretax income dispersion and comparatively weak redistribution at the top of the income distribution.
Keywords: economics; policy